The supernumerary cheek tooth in tabby/EDA mice-a reminiscence of the premolar in mouse ancestors - Peterková, R; Lesot, H; Viriot, L; Peterka, M (Archives of oral biology, 2005)
OBJECTIVE: A supernumerary cheek tooth occurs mesially to the first molar in tabby/EDA (Ta) mice affected by hypohidrotic ectodermal dysplasia. The supernumerary tooth (S) has been hypothetically homologized to the premolar, which has disappeared during mouse evolution. DESIGN: This hypothesis was tested using available morphological data on the lower cheek teeth in wild type (WT) and Ta mice. RESULTS: The presence of S is accompanied by a reduction in the mesial portion of the M(1) in mutant mice. 3D reconstructions suggest that the S in Ta homo/hemizygous embryos originates from a split off the mesial portion of the first molar (M(1)) cap. In WT embryos, two vestigial tooth primordia are transiently distinct in front of the M(1). The distal vestige has the form of a wide bud and participates during the development of the mesial portion of the M(1). This bud has been homologized with the vestigial primordium of the fourth premolar of mouse ancestors. The premolar disappearance coincided with a mesial lengthening of the M(1) during mouse evolution. The incorporation of the distal premolar vestige into the mesial part of the M(1) in WT embryos can be regarded as a repetition of the premolar disappearance during evolution. CONCLUSION: : Ontogenetic and phylogenetic data support that the S in Ta mice arises due to the segregation of the distal premolar vestige from the molar dentition and thus represents an evolutionary throwback (atavism).
Keywords: mutantní kmeny myší; zuby přespočetné; homozygot; Tooth, Supernumerary; tvář; ektodermální dysplazie; ektodysplasiny; membránové proteiny; Membrane Proteins; biologická evoluce; Homozygote; Mice, Mutant Strains; Animals; Biological Evolution; zvířata; myši; Ectodysplasins; Cheek; Bicuspid; Mice; Ectodermal Dysplasia; premolár